DESIGNING AN E-KANBAN SYSTEM TO IMPROVE DRUG AVAILABILITY AND MINIMISE INVENTORY WASTE AT THE HOSPITAL PHARMACY INSTALLATION - Sriyanto, Sriyanto; Dyah Ika, Rinawati (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
In an effort to provide a high level of service to hospitals, pharmaceutical installations are often faced with problems in monitoring and determining adequate drug supply levels to respond to demand, both from outpatient and inpatient units. Inventory control by hospital pharmacies is often carried out without being supported by accurate information systems or control methods, resulting in excess inventory levels which leads to higher inventory costs. This study aims to identify and develop an e-kanban system suitable for the scope of hospital pharmacy. E-kanban as a method of controlling inventory through a simple reliable information system is expected to minimize inventory waste that occurs. The e-kanban system coupled with the use of barcodes and portable scanners is expected to provide more accurate information on drug availability. Inventory monitoring and control is expected to be much easier, both at the time of replenishment and during periodic stock-taking. The implementation of the e-kanban system is also able to eliminate waste, card use and manual recording activities, replaced by the use of simpler two-bin containers. The e-kanban system can also be integrated into the existing Hospital Information System, without disrupting the running system.